Comparative Figurative Language In Justin Bieber’s Song Lyrics - Silalahi, Yeftasedek; Heryono, Heri (Universitas Nahdlatul Wathan Mataram, 2024)
People use figurative language in order to express themselves. There are many types of figurative language, one of which is comparative figurative language. The objectives of this research are to find out the classification and the types of comparative figurative language found in Justin Bieber’s song lyrics and look for non-literal meanings in them. This research uses a qualitative method to find the types of comparative figurative language and the meaning in the song lyrics.The main data for this research were taken from the lyrics of Justin Bieber’s song containing figurative language, which focused on the classification of comparative figurative language. Since the data analysis was done by collecting, analysing, classifying the data and presenting the results of data analysis, the descriptive research approach was employed in this study. From the analysed data, this research found a total of 42 lyrics that contained comparative figurative language. Personification dominates with the highest total number of 19 (45%), followed by simile with a total number of 16 (38%), and the researcher also found metaphor with a total number of 7 (17%). There are 1 living personification, 8 non-living personifications, 10 abstract personifications, 4 open similes, 12 closed similes, 1 anthropomorphic metaphor, and 6 concrete to abstract metaphors.